Fecundity disorders in older women: declines in follicular development and endometrial receptivity - Wang, Li (BMC Womens Health, 2020)
BACKGROUND: Little research is available on follicular development and endometrial receptivity in older women. This study aimed to assess follicular development and endometrial receptivity, and to evaluate ultrasonic parameters in predicting endometrial receptivity during the implantation window in older women. METHODS: For this prospective case-control study, 224 older women and 215 young women were recruited. The follicular development and endometrial thickness were monitored by transvaginal ultrasound. During the implantation window, the pulsatility index (PI) and resistance index (RI) of the uterine arteries and subendometrial region, endometrial volume, vascularization index (VI), flow index (FI) and vascularization flow index (VFI) were calculated between the two groups. The ultrasonic parameters were used to assess endometrial receptivity in older women. RESULTS: The serum anti-Mullerian hormone (AMH) concentration and antral follicle count (AFC) were significantly lower in older women than in young women. The average diameter of the dominant follicle on days 14, 16, and 18 of the menstrual cycle were significantly smaller, and the subendometrial region RI on days 12, 14, 16, and 18 of the menstrual cycle were significantly higher in older women than in young women. The normal ovulation rate was significantly lower in older women than in young women. The subendometrial region RI was significantly higher, and the endometrial VI, FI, and VFI were significantly lower in older women compared with young women. The biochemical pregnancy rate, clinical pregnancy rate and ongoing pregnancy rate of older women were significantly lower than in young women. The best ultrasonic parameter for predicting endometrial receptivity during the implantation window in older women was VI (AUC =0.889, sensitivity 92.6% and specificity 85.4%). CONCLUSIONS: Older women present decreased serum AMH concentrations and AFC, defined as indicators of ovarian reserve function. Older women are characterized by decreased follicular development and endometrial receptivity, which may lead to fecundity disorders.